Faktor-Faktor yang Mempengaruhi Pengeluaran Rumah Tangga Miskin di Desa Keramas, Kabupaten Gianyar - pratama, i putu yogi; Marhaeni, AnakAgung Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700], 2022)
ABSTRACT The problem of poverty in Gianyar Regency is that the poverty rate is still relatively high. Therefore poverty is a shared responsibility. The aims of this study are: 1) to analyze the simultaneous effect of household income, intensity of traditional and religious activities, household consumption, and number of household members on the expenditure of poor households in Keramas Village, Gianyar Regency, 2) to analyze the partial effect of household income. households, the intensity of traditional and religious activities, household consumption, and the number of household members on the expenditure of  poor households in Keramas Village, Gianyar Regency, 3) to analyze the role of the number of household members in moderating the effect of consumption on the  expenditure of poor households in Keramas Village. , Gianyar Regency. The population in this study were 157 poor households in Keramas Village, Gianyar Regency using the Slovin formula, then 61 poor households were obtained. The sampling method is Stratified Random Sampling with the type of Proportionate Stratified Random Sampling and data collection techniques through observation, interviews, and in-depth interviews. The analytical technique used in this research is Moderation Regression Analysis. The results of the study show the results: 1) household income, household consumption, the intensity of traditional and religious activities, and the intensity of traditional and religious activities simultaneously have a significant effect on the expenditure of poor households in Keramas Village, Gianyar Regency, 2) household income, household consumption, and the number of household members partially have a positive and significant effect on the expenditure of poor households in Keramas Village, Gianyar Regency, the variable intensity of traditional and religious activities has no effect on the expenditure of poor households in Keramas Village, Gianyar Regency, 3) the number of family members weaken the influence of household consumption variables on the expenditures of poor households in Keramas Village, Gianyar Regency.     Keywords:     income, intensity of customary activities, household consumption, number of family members, poor household expenditure